Does cardiac transplant protect against broken hearts?. (25th November 2020) - Isath, A; Perembeti, S; Correa, A; Rao, S; Chahal, A; Padmanabhan, D; Contreras, J; Garg, V
Abstract: Background: Takotsubo cardiomyopathy (TC) is a reversible stress-induced myocardial dysfunction with increased sympathetic activity caused by excessive release of catecholamines playing a central role in its pathophysiology. The occurrence of TC in transplanted hearts is rare given the complete denervation done during transplantation. However, it has been demonstrated that 40% of transplant recipients undergo sympathetic re-innervation. There have only been case reports describing TC in post-transplant recipients. Purpose: To evaluate the incidence, baseline characteristics and outcomes of TC occurring in heart transplant recipients using Healthcare Cost and Utilization Project (HCUP) National (nationwide) Inpatient Sample (NIS) in United States from 2009 to 2014. Methods: Using NIS data, we identified patients who underwent cardiac transplantation using ICD9 procedure codes 37.5 and 33.6. Among these patients, we identified those admitted to the hospital with diagnosis of TC based on ICD-9-CM code 429.83. We presented categorical data as percentages and continuous data as mean or median as appropriate. Results: We identified 257 hospitalizations for TC in heart transplant recipient patients. There was an approximately 9-fold increase in admissions from 11 in 2009 to 95 in 2014. Among patients with TC, the mean age was 65.3±1.8 years and majority were female (76.6%). A majority of patients were Caucasians (63%) followed by smaller proportion of African-Americans (13.2%). In-patient mortality in patients admitted with TC following heart transplant was 11.3% (n=29). During the hospitalization, 4.8% of patients had cardiogenic shock and 2.8% required mechanical circulatory support. The average length of stay for patients with TC was 16.6±3.3 days. The mean cost of hospitalization for these patients when adjusted for inflation were 237248±55709 dollars. Conclusion: TC can still occur in substantially in heart transplant recipients and should be considered one of the differential diagnosis in transplant patients presenting to the hospital. Funding Acknowledgement: Type of funding source: None